Expected Log-Utility Maximization Under Incomplete Information and with Cox-Process Observations

Abstract

We consider the portfolio optimization problem for the criterion of maximization of expected terminal log-utility. The underlying market model is a regime-switching diffusion model where the regime is determined by an unobservable factor process forming a finite state Markov process. The main novelty is due to the fact that prices are observed and the portfolio is rebalanced only at random times corresponding to a Cox process where the intensity is driven by the unobserved Markovian factor process as well. This leads to a more realistic modeling for many practical situations, like in markets with liquidity restrictions; on the other hand it considerably complicates the problem to the point that traditional methodologies cannot be directly applied. The approach presented here is specific to the log-utility. For power utilities a different approach is presented in the companion paper (Fujimoto et al. in Appl Math Optim 67(1):33–72, 2013).

This is a preview of subscription content, log in to check access.

Notes

  1. 1.

    We are grateful for an anonymous suggestion of this useful norm.

References

  1. Atar, R., Zeitouni, O. (1997). Exponential stability for nonlinear filtering. Annales de l’Institut Henri Poincare (B) Probability and, Statistics, 33, 697–725.

  2. Bäuerle, N., & Rieder, U. (2011). Markov decision processes with applications to finance. Berlin: Springer, Universitext.

    Google Scholar 

  3. Björk, T., Davis, M. H. A., & Landén, C. (2010). Optimal investment under partial information. Mathematical Methods of Operations Research, 71, 371–399.

    Google Scholar 

  4. Bremaud, P. (1981). Point processes and queues: Martingale dynamics. New York: Springer.

    Google Scholar 

  5. Capponi, A., & Figueroa-Lopez, J. E. (2013). Power utility maximization in hidden regime-switching markets with default risk. http://arxiv.org/abs/1303.2950

  6. Callegaro, G., Di Masi, G. B., & Runggaldier, W. J. (2006). Portfolio optimization in discontinuous markets under incomplete information. Asia Pacific Financial Markets, 13(4), 373–394.

    Article  Google Scholar 

  7. Cvitanic, J., Liptser, R., & Rozovski, B. (2006). A filtering approach to tracking volatility from prices observed at random times. The Annals of Applied Probability, 16, 1633–1652.

    Article  Google Scholar 

  8. Cvitanic, J., Rozovski, B., & Zaliapin, I. (2006). Numerical estimation of volatility values from discretely observed diffusion data. Journal of Computational Finance, 9, 1–36.

    Google Scholar 

  9. Elliott, R. J., Aggoun, L., & Moore, J. B. (1995). Hidden Markov models: Estimation and control. New York: Springer.

    Google Scholar 

  10. Frey, R., & Runggaldier, W. (2001). A nonlinear filtering approach to volatility estimation with a view towards high frequency data. International Journal of Theoretical and Applied Finance, 4, 199–210.

    Article  Google Scholar 

  11. Fujimoto, K., Nagai, H., & Runggaldier, W. J. (2013). Expected power-utility maximization under incomplete information and with Cox-process observations. Applied Mathematics and Optimization, 67(1), 33–72.

    Article  Google Scholar 

  12. Gassiat, P., Gozzi, F., & Pham, H. (2011a). Investment/consumption problems in illiquid markets with regimes switching (preprint).

  13. Gassiat, P., Pham, H., & Sirbu, M. (2011b). Optimal investment on finite horizon with random discrete order flow in illiquid markets. International Journal of Theoretical and Applied Finance, 14, 17–40.

    Article  Google Scholar 

  14. Goll, T., & Kallsen, J. (2003). A complete explicit solution to the log-optimal portfolio problem. The Annals of Applied Probability, 13, 774–799.

    Article  Google Scholar 

  15. Grandell, J. (1991). Aspects of risk theory. New York: Springer.

    Google Scholar 

  16. Le Gland, F., & Oudjane, N. (2004). Stability and uniform approximation of nonlinear filters using the Hilbert metric, and application to particle filters. Annals of Applied Probability, 14(1), 144–187.

    Article  Google Scholar 

  17. Liverani, C. (1995). Decay of correlations. The Annals of Mathematics, 142(2), 239–301.

    Article  Google Scholar 

  18. Matsumoto, K. (2006). Optimal portfolio of low liquid assets with a log-utility function. Finance and Stochastics, 10, 121–145.

    Article  Google Scholar 

  19. Nagai, H. (2004). Risky fraction processes and problems with transaction costs. In J. Akahori et al. (Ed.), Stochastic processes and applications to mathematical finance (pp. 271–288) World Scientific.

  20. Pham, H. (2011). Portfolio optimization under partial information: Theoretical and numerical aspects. In D. Crisan & B. Rozovskii (Eds.), The Oxford handbook on nonlinear filtering (pp. 990–1018). Oxford: Oxford University Press.

    Google Scholar 

  21. Platen, E., & Runggaldier, W. J. (2007). A benchmark approach to portfolio optimization under partial information. Asia Pacific Financial Markets, 14, 25–43.

    Article  Google Scholar 

  22. Pham, H., & Tankov, P. (2008). A model of optimal consumption under liquidity risk with random trading times. Mathematical Finance, 18, 613–627.

    Article  Google Scholar 

  23. Pham, H., & Tankov, P. (2009). A coupled system of integrodifferential equations arising in liquidity risk models. Applied Mathematics and Optimization, 59, 147–173.

    Article  Google Scholar 

  24. Rogers, L. C. G., & Zane, O. (2002). A simple model of liquidity effects. In K. Sandmann & P. Schönbucher (Eds.), Advances in finance and stochastics, essays in honour of Dieter Sondermann (pp. 161–176). Berlin: Springer.

  25. Taksar, M., & Zeng, X. (2007). Optimal terminal wealth under partial information: Both the drift and the volatility driven by a discrete-time Markov chain. SIAM Journal on Control and Optimization, 46(4), 1461–1482.

    Article  Google Scholar 

Download references

Author information

Affiliations

Authors

Corresponding author

Correspondence to Kazufumi Fujimoto.

Additional information

The opinions expressed are those of the author and not those of The Bank of Tokyo-Mitsubishi UFJ.

Appendix

Appendix

Proof of Lemma 4.1

Proof of statement (i). It follows from the two lemmas shown below.

Lemma 5.1

We have the following representation,

$$\begin{aligned} E\left[ f(\theta _t,h_t )|\mathcal{G }_t\right] \!=\!\displaystyle \sum _{k\ge 0}1_{]\tau _k, \tau _{k+1}]}(t) \frac{E\left[ f\left( \theta _t, \gamma \left( {\tilde{X}}_t \!-\! \tilde{X}_{\tau _k}, h_k\right) \right) 1_{\{ t\le \tau _{k+1} \} } |\mathcal{G }_k \right] }{ E\left[ 1_{\{ t\le \tau _{k+1} \} } |\mathcal{G }_k \right] }.\qquad \quad \end{aligned}$$
(5.1)

Proof

It suffices to prove that for any \(\mathcal{G }_t-\)adapted process \(Z_t\)

$$\begin{aligned}&E\left[ E\left[ f(\theta _t,h_t )|\mathcal{G }_t\right] Z_t\right] \nonumber \\&\quad {=}E\left[ \!\displaystyle \sum _{k\ge 0}1_{]}\tau _k, \tau _{k+1}](t) \frac{E\!\left[ \!f\left( \!\theta _t ,\gamma \left( \!{\tilde{X}}_t {-} \tilde{X}_{\tau _k}, h_k\!\right) \right) 1_{\{ t\le \tau _{k+1} \} } |\mathcal{G }_k \!\right] }{E\left[ 1_{\{ t\le \tau _{k+1} \} } |\mathcal{G }_k \right] }\, Z_t\!\!\right] \!.\nonumber \\ \end{aligned}$$
(5.2)

First notice that any \(\mathcal{G }_t-\)adapted process \(Z_t\) has the representation (see Bremaud 1981)

$$\begin{aligned} Z_t = \displaystyle \sum _{k\ge 0}1_{]\tau _k, \tau _{k+1}]}(t) Z_k(t) + Z_{\infty }1_{]\tau _\infty , \infty [ }(t) , \end{aligned}$$
(5.3)

with the process \(Z_k(t)\) being \(\mathcal{G }_k \otimes \mathcal{B }(\mathbb{R }_+)\)-measurable. Furthermore, under our assumptions, for all \(t>0, \lim _{n\rightarrow \infty }1_{ \{ \tau _n < t\} } =0\) and thus

$$\begin{aligned} Z_t = \displaystyle \sum _{k\ge 0}1_{]\tau _k, \tau _{k+1}]}(t) Z_k(t). \end{aligned}$$
(5.4)

Note, finally, that \(E\left[ 1_{\{\tau _k< t\le \tau _{k+1} \}} |\mathcal{G }_k \right] =1_{]\tau _k, \infty )} (t) E[1_{\{ t\le \tau _{k+1} \}}|\mathcal{G }_k ]] \). We then have

$$\begin{aligned} E\left[ E\left[ f(\theta _t,h_t )|\mathcal{G }_t\right] Z_t\right]&= E[f(\theta _t,h_t )\displaystyle \sum _{k\ge 0}1_{]\tau _k, \tau _{k+1}]}(t) Z_k(t)] \\&= \displaystyle \sum _{k\ge 0}E\left[ E\left[ f(\theta _t,h_t )1_{\{ t\le \tau _{k+1} \} }|\mathcal{G }_k\right] 1_{\{ \tau _k <t \} } Z_k(t)\right] \\&= \displaystyle \sum _{k\ge 0}E\Bigg [\!\frac{E\left[ f(\theta _t,h_t )1_{\{ t\le \tau _{k+1} \} }|\mathcal{G }_k\right] }{ E[1_{\{ t\le \tau _{k+1} \} } |\mathcal{G }_k ]} E\Bigg [\! 1_{]\tau _k, \tau _{k+1}]}(t) Z_k(t)|\mathcal{G }_k\Bigg ]\Bigg ] \\&= \displaystyle E[\sum _{k\ge 0} 1_{]\tau _k, \tau _{k+1}]}(t)\frac{E\left[ f(\theta _t,h_t ) 1_{\{ t\le \tau _{k+1} \} }|\mathcal{G }_k\right] }{ E[1_{\{ t\le \tau _{k+1} \} } |\mathcal{G }_k ]} Z_t], \end{aligned}$$

and thus we obtain (5.2) since

$$\begin{aligned} f(\theta _t ,h_t)&= \displaystyle \sum _{k=0}^{\infty } 1_{[\tau _{k},\tau _{k+1})}(t) f(\theta _t ,\gamma (\tilde{X}_t - \tilde{X}_{\tau _k}, h_k)), \end{aligned}$$

which follows from (2.16). \(\square \)

Lemma 5.2

We have the following equation

$$\begin{aligned}&E\left[ \int \limits _t^T f(\theta _s,h_s )ds | \tau _0 = t, \pi _{\tau _0} = \pi \right] \nonumber \\&\quad =E\left[ \displaystyle \sum _{k\ge 0} \hat{C}(\tau _k,\pi _{\tau _k},h_k) 1_{ \{ \tau _k <T \} } | \tau _0 = t, \pi _{\tau _0} = \pi \right] \end{aligned}$$
(5.5)

with \(\hat{C}(t,\pi ,h)\) defined by (4.6) in Definition 4.1.

Proof

For simplicity, in the following formula we shall use the notation

$$\begin{aligned} E^{t,\pi }[\cdot ]\equiv E[\cdot \;|\tau _0=t, \pi _{\tau _0}=\pi ] \end{aligned}$$

Using (5.1) we have similarly as above

$$\begin{aligned}&E^{t,\pi }\left[ \int \limits _t^T E\left[ f(\theta _s ,h_s)|\mathcal{G }_s\right] ds \right] \nonumber \\&\quad =E^{t,\pi }\left[ \int \limits _t^T \displaystyle \sum _{k\ge 0}1_{]\tau _k, \tau _{k+1}]}(s) \frac{E\left[ f(\theta _s ,\gamma (\tilde{X}_s - \tilde{X}_{\tau _k}, h_k))1_{\{ s< \tau _{k+1} \} } |\mathcal{G }_k \right] }{ E\left[ 1_{\{ s\le \tau _{k+1} \} } |\mathcal{G }_k \right] } ds \right] \nonumber \\&\quad =E^{t,\pi }\left[ \displaystyle \sum _{k\ge 0} \int \limits _t^T 1_{]\tau _k, \infty )} (s) E\left[ f(\theta _s ,\gamma (\tilde{X}_s - \tilde{X}_{\tau _k}, h_k)) 1_{\{ s< \tau _{k+1} \} } |\mathcal{G }_k \right] ds \right] \nonumber \\&\quad =E^{t,\pi }\left[ \displaystyle \sum _{k\ge 0} \int \nolimits _t^T 1_{]\tau _k, \infty )} (s) E\left[ e^{ -\int \nolimits _{\tau _k}^s n(\theta _u)du }f(\theta _s ,\gamma (\tilde{X}_s - \tilde{X}_{\tau _k}, h_k)) |\mathcal{G }_k \right] ds \right] \nonumber \\&\quad =E^{t,\pi }\left[ \displaystyle \sum _{k\ge 0} \int \limits _t^T 1_{]\tau _k, \infty )} (s) E\left[ E[e^{ -\int \nolimits _{\tau _k}^s n(\theta _u)du } f(\theta _s ,\gamma (\tilde{X}_s - \tilde{X}_{\tau _k}, h_k)) |\mathcal{G }_k \vee \sigma \{ \theta _{\tau _k} \} ]|\mathcal{G }_k \right] ds\right] \nonumber \\ \end{aligned}$$
(5.6)

Since \(\left( \theta _t, \tilde{X}_t\right) \) is a time homogeneous Markov process,

$$\begin{aligned}&E\left[ e^{ -\int \nolimits _{\tau _k}^s n(\theta _u)du } f\left( \theta _s ,\gamma \left( \tilde{X}_s - \tilde{X}_{\tau _k}, h_k\right) \right) |\mathcal{G }_k \vee \sigma \{ \theta _{\tau _k} \} \right] \nonumber \\&\quad =E\!\left[ \!e^{ -\int \nolimits _{0}^t n(\theta _u)du } f\left( \theta _t ,\gamma \left( \tilde{X}_t - x, h\right) \right) \bigg | \theta _0 =\theta , \tilde{X}_0=x\right] \bigg |_{t=s-\tau _k, \theta =\theta _k,x=\tilde{X}_{\tau _k},h=h_k }\nonumber \\ \end{aligned}$$
(5.7)

We now have, recalling the definition of \(r_{ji}(t,z)\) in (3.8),

$$\begin{aligned}&E\left[ e^{ -\int \nolimits _{0}^t n(\theta _s)ds)} f\left( \theta _t ,\gamma \left( \tilde{X}_t - x, h\right) \right) | \theta _0 =\theta , \tilde{X}_0=x\right] \nonumber \\&\quad =E\left[ e^{ -\int \nolimits _{0}^t n(\theta _s)ds ) }E\left[ f(\theta _t ,\gamma (\tilde{X}_t - x, h)) \bigg | \mathcal{F }^{\theta }_t\vee \{\tilde{X}_0=x\} \right] \bigg | \theta _0 =\theta , \tilde{X}_0=x\right] \nonumber \\&\quad =E\left[ e^{ -\int \nolimits _{0}^t n(\theta _s)ds ) }\int \limits _{\mathbb{R }^m}f(\theta _t ,\gamma ( z , h)) \rho ^{\theta }_{0,t} (z) dz \bigg |\theta _0 =\theta , \tilde{X}_0=x\right] \nonumber \\&\quad =E\left[ \,\,\,\int \limits _{\mathbb{R }^m} \sum \limits _{ij} 1_{ \{ \theta _t = e_i , \theta _0 = e_j \} } f(e_i ,\gamma ( z , h))\right. \nonumber \\&\quad \quad \left. \times E\left[ e^{ -\int \limits _{0}^t n(\theta _s)ds } \rho ^{\theta }_{0,t} (z) | \theta _t = e_i , \theta _0 = e_j \right] dz \bigg |\theta _0 =\theta , \tilde{X}_0=x\right] \nonumber \\&\quad =E\left[ \,\,\,\int \limits _{\mathbb{R }^m} \sum \limits _{ij} 1_{ \{ \theta _t = e_i , \theta _0 = e_j \} } f(e_i ,\gamma ( z , h)) r_{ji}(t,z) dz \bigg |\theta _0 =\theta , \tilde{X}_0=x\right] \nonumber \\&\quad =\int \limits _{\mathbb{R }^m} \sum \limits _{ij} f(e_i ,\gamma ( z , h)) r_{ji}(t,z) p_{ji}(t) 1_{ \{ \theta = e_j \} }dz. \end{aligned}$$
(5.8)

We finally have

$$\begin{aligned}&E^{t,\pi }\left[ \int \limits _t^T f(\theta _s,h_s )ds \right] =E^{t,\pi }\left[ \int \limits _t^T E[f(\theta _s ,h_s)|\mathcal{G }_s] ds \right] \nonumber \\&\quad =E^{t,\pi }\left[ \displaystyle \sum _{k\ge 0} \int \limits _t^T 1_{]\tau _k, \infty )} (s) E[E[e^{ -\int \limits _{\tau _k}^s n(\theta _u)du } f(\theta _s ,\gamma (\tilde{X}_s - \tilde{X}_{\tau _k}, h_k)) |\mathcal{G }_k \vee \sigma \{ \theta _{\tau _k} \} ]|\mathcal{G }_k ] ds \right] \nonumber \\&\quad =E^{t,\pi }\left[ \displaystyle \sum _{k\ge 0} 1_{ \{ \tau _k <T \} } \int \limits _{\tau _k}^T \int \limits _{\mathbb{R }^m} \sum \limits _{ij} f(e_i , \gamma (z ,h_k)) r_{ji}(s-\tau _k, z) p_{ji}(s-\tau _k) \pi _{\tau _k}^j dzds \right] \nonumber \\&\quad =E^{t,\pi }\left[ \displaystyle \sum _{k\ge 0} \hat{C}(\tau _k,\pi _{\tau _k},h_k) 1_{ \{ \tau _k <T \} } \right] . \end{aligned}$$
(5.9)

\(\square \)

Proof of statement (ii) of Lemma 4.1.

We start by proving that \(\hat{C}(t,\pi , h)\) is Lipschitz continuous with respect to \(t\).

$$\begin{aligned} \hat{C}(t,\pi , h)&= \int \limits _{ t}^{T} \int \limits _{\mathbb{R }^m}\sum \limits _{i,j} f(e_i ,\gamma (x, h))r_{ji}(s-t,x)p_{ji}(s-t)\pi ^j dxds \nonumber \\&= \int \limits _{ 0}^{T-t} \int \limits _{\mathbb{R }^m}\sum \limits _{i,j} f(e_i ,\gamma (x, h))r_{ji}(s,x)p_{ji}(s)\pi ^j dxds . \end{aligned}$$
(5.10)

Thus

$$\begin{aligned} \left| \hat{C}(t,\pi , h)-\hat{C}(\bar{t},\pi , h)\right|&= \left| \,\,\int \limits _{T - \bar{t}}^{T - t} \int \limits _{\mathbb{R }^m}\sum \limits _{i,j} f(e_i ,\gamma (x, h))r_{ji}(s,x)p_{ji}(s)\pi ^j dxds \right| \nonumber \\&\le \Vert f \Vert |t-\bar{t}| , \end{aligned}$$
(5.11)

where \(\Vert f \Vert := \sup _{e\in E, h\in \bar{H}_m}\Vert f(e, h) \Vert \). Next, let us prove that \(C(t,\pi , h)\) is Lipschitz continuous with respect to \(\pi \) [in the metric introduced in (3.21)].

$$\begin{aligned} \left| \hat{C}(t,\pi , h){-}\hat{C}(t,\bar{\pi }, h)\right|&= \left| \int \limits _{0}^{T - t} \int \limits _{\mathbb{R }^m}\sum \limits _{i,j} f(e_i ,\gamma (x, h))r_{ji}(s,x)p_{ji}(s)(\pi ^j {-}\bar{\pi }^j )dxds \right| \nonumber \\&\le \Vert f \Vert T |\pi -\bar{\pi }|= \Vert f \Vert T \sum _{i=1}^N |\pi (e_i)-\bar{\pi }(e_i)| \nonumber \\&\le \Vert f \Vert T \Vert \pi -\bar{\pi } \Vert _{TV} \le \Vert f \Vert T \frac{2}{\log 3}d_H(\pi , \bar{\pi }) , \end{aligned}$$
(5.12)

where we have used (3.20).

Next, let us prove that \(C(t,\pi , h)\) is continuous with respect to \(h\) [always in the metric introduced in (3.21)]. The function \(f(e_i,h)\) is bounded and continuous with respect to \(h\) for all \(i\). Furthermore, \(\gamma (x,h)\) is continuous with respect to \(h\) for all \(x\in \mathbb{R }^m\). Applying the dominated convergence theorem, for \(\ {h_n}\subset \bar{H}_m\), s.t.\(\displaystyle \lim _{n\rightarrow \infty } h_n =h\in \bar{H}_m\)

$$\begin{aligned} \displaystyle \lim _{n\rightarrow \infty } \hat{C}(t,\pi , h_n)&= \int \limits _{0}^{T - t} \int \limits _{\mathbb{R }^m}\sum \limits _{i,j} \displaystyle \lim _{n\rightarrow \infty } f(e_i , \gamma (x, h_n))r_{ji}(s,x)p_{ji}(s)\pi ^j dxds \nonumber \\&= \int \limits _{0}^{T - t} \int \limits _{\mathbb{R }^m}\sum \limits _{i,j} f(e_i ,\gamma (x, h))r_{ji}(s,x)p_{ji}(s)\pi ^j dxds \nonumber \\&= \hat{C}(t,\pi , h). \end{aligned}$$
(5.13)

\(\hat{C}(t,\pi , h)\) is thus continuous with respect to each of the variables \(t,\pi ,h\). However, continuity in \(t,\pi \) is independent of the other variable. Hence, \(\hat{C}(t,\pi , h)\) is a continuous function on \([0,T]\times \mathcal{S }_N \times \bar{H}_m\).

Proof of Lemma 4.2

Fix \(n\ge 0\). Recall the definition of \( h_{n}^i\) given in Sect. 2.3. Since \(S_t\) is continuous and \(V_t\) satisfies the self-financing condition, we obtain

$$\begin{aligned} h_{\tau _{n}-}^i=\frac{N_{n-1}^iS_{\tau _{n}-}^i}{V_{\tau _{n}-}} = \frac{N_{n-1}^iS_{\tau _{n}}^i}{V_{\tau _{n}}} =\frac{N_{n-1}^iS_{\tau _{n}}^i}{\sum _{i=0}^mN_{n}^iS_{\tau _{n}}^i}. \end{aligned}$$

Using (2.16), (2.18), for \( all \ k\ge 1,h \in \mathcal{A }^{n},t\in [\tau _{n+k},T]\), one furthermore has

$$\begin{aligned} h^i_t= \gamma ^i(\tilde{X}_t - \tilde{X}_{\tau _{n+k}}, h_{n+k}) =\gamma ^i(\tilde{X}_t - \tilde{X}_{\tau _n}, h_{n}) . \end{aligned}$$

Therefore, using lemma 4.1(i) for \(\ h\in \mathcal{A }^n\)

$$\begin{aligned}&W(t,\pi , h.) = E\left[ \displaystyle \sum _{k=0}^{n -1} \int \limits _{\tau _{k}}^{T\wedge \tau _{k+1}} f(\theta _s ,\gamma (\tilde{X}_s - \tilde{X}_{\tau _k}, h_k)) ds 1_{\{\tau _{k}<T\}}\right. \nonumber \\&\quad \left. + \ \displaystyle \sum _{k=n}^{\infty } \int \limits _{\tau _{k}}^{T\wedge \tau _{k+1}} f(\theta _s , \gamma (\tilde{X}_s - \tilde{X}_{\tau _k}, h_k)) ds 1_{\{\tau _{k}<T\}} | \tau _0=t,\;\pi _{\tau _0}=\pi \right] \nonumber \\&= E\left[ \displaystyle \sum _{k=0}^{n-1 } \hat{C}(\tau _k,\pi _{\tau _k}, h_k)1_{\{\tau _{k}<T\}}+ \ \int \limits _{\tau _{n}}^{T} f\left( \theta _s ,\gamma \left( \tilde{X}_s - \tilde{X}_{\tau _n}, h_n\right) \right) ds1_{\{\tau _{n}<T\}} | \tau _0=t,\;\pi _{\tau _0}=\pi \right] .\nonumber \\ \end{aligned}$$
(5.14)

Proof of Lemma 4.6

By the definition of \(\mathcal{A }^n\), for \(n\ge 0, \mathcal{A }^n\subset \mathcal{A }^{n+1} \subset \mathcal{A }\), hence,

$$\begin{aligned} \displaystyle \sup _{h \in \mathcal{A }^n} W(t,\pi ,h.) \le \displaystyle \sup _{h \in \mathcal{A }^{n+1}} W(t,\pi ,h.) \le \displaystyle \sup _{h \in \mathcal{A }} W(t,\pi ,h.) . \end{aligned}$$
(5.15)

By the definition of \(W^{n}(t,\pi ) \) and \(W(t,\pi ) \)

$$\begin{aligned} W^{n}(t,\pi ) \le W^{n+1}(t,\pi ) \le W(t,\pi ) . \end{aligned}$$
(5.16)

Using Lemma 4.5, for \(\ n,m\ge 0\)

$$\begin{aligned} \bar{W}^{n}(t,\pi ) \le \bar{W}^{n+m}(t,\pi ) \le W(t,\pi ) . \end{aligned}$$
(5.17)

Letting \(m\rightarrow \infty \)

$$\begin{aligned} \bar{W}^{n}(t,\pi ) \le \bar{W}(t,\pi ) \le W(t,\pi ) . \end{aligned}$$
(5.18)

Proof of Lemma 4.7

For\( \ h \in \mathcal{A }, W(t,\pi ,h)\) defined by (4.8) satisfies

$$\begin{aligned} W(t,\pi ,h.)&= E\left[ \displaystyle \sum _{k=0}^{n-1 } \hat{C}(\tau _k,\pi _{\tau _k} ,h_k)1_{\{\tau _{k}<T\}} |\tau _0=t,\pi _{\tau _0}=\pi \right] \nonumber \\&\quad + \ E \left[ \displaystyle \sum _{k=n}^{\infty } \hat{C}\left( \tau _k,\pi _{\tau _k}, h_k\right) 1_{\{\tau _{k}<T\}} |\tau _0=t,\pi _{\tau _0}=\pi \right] \nonumber \\&= E\left[ \displaystyle \sum _{k=0}^{n-1 } \hat{C}(\tau _k,\pi _{\tau _k}, h_k)1_{\{\tau _{k}<T\}}+ \int \limits _{\tau _{n}}^{T} f\left( \theta _s ,\gamma \left( \tilde{X}_s - \tilde{X}_{\tau _n}, h_n\right) \right) ds1_{\{\tau _{n}<T\}} \right. \nonumber \\&\quad \left. - \ \int \limits _{\tau _{n}}^{T} f(\theta _s ,\gamma (\tilde{X}_s - \tilde{X}_{\tau _n}, h_n)) ds1_{\{\tau _{n}<T\}} |\tau _0=t,\pi _{\tau _0}=\pi \right] \nonumber \\&\quad + \ E[W(\tau _n,\pi _{\tau _n}, h.)1_{\{\tau _{n}<T\}} |\tau _0=t,\pi _{\tau _0}=\pi ]. \nonumber \\&\le W^n(t,\pi )+\left| E \left[ \int \limits _{\tau _{n}}^{T} f\left( \theta _s ,\gamma \left( \tilde{X}_s - \tilde{X}_{\tau _n}, h_n\right) \right) ds1_{\{\tau _{n}<T\}} |\tau _0=t,\pi _{\tau _0}=\pi \right] \right| \nonumber \\&\quad + \ E\left[ W(\tau _n,\pi _{\tau _n}, h.)1_{\{\tau _{n}<T\}} |\tau _0=t,\pi _{\tau _0}=\pi \right] \nonumber \\&\le {\bar{W}}^n(t,\pi )+2\Vert f \Vert T P(\tau _{n}<T | \tau _{0}=t). \end{aligned}$$
(5.19)

because of the representation of \(W^n(t,\pi )\) in Corollary 4.2 (Eq. 4.13) and Lemma 4.5. Thus, by letting \(n \rightarrow \infty \), we obtain

$$\begin{aligned} W(t,\pi ,h.) \le \bar{W}(t,\pi ) \end{aligned}$$
(5.20)

for all \( \ h \in \mathcal{A }\).

Rights and permissions

Reprints and Permissions

About this article

Cite this article

Fujimoto, K., Nagai, H. & Runggaldier, W.J. Expected Log-Utility Maximization Under Incomplete Information and with Cox-Process Observations. Asia-Pac Financ Markets 21, 35–66 (2014). https://doi.org/10.1007/s10690-013-9176-1

Download citation

Keywords

  • Portfolio optimization
  • Stochastic control
  • Incomplete information
  • Regime-switching models
  • Cox-process observations
  • Random trading times